The case for patient-reported pleasure - Preston Long; Tanja Stamm (The Beryl Institute, 2023)
Pleasure is a cornerstone of human behavior. Its lack of consideration in the medical sciences has been to the detriment of all patients. The process of including pleasure as a medical outcome has multiple beginnings. A health-related pleasure scale must be developed for clinical purposes and original research must be conducted to establish the added value of measuring pleasure. Treatment comparisons, prediction models for recovery, side-effect investigations, and more may benefit from the collection of patient-reported pleasure. Furthermore, simply inquiring about a patient's pleasure may serve as a positive intervention by giving them permission to discuss more than the illness in their life. This can enhance the patient-provider relationship and expand the goal of treatment from illness elimination to wellness expansion. Reporting on pleasure can also benefit patients by reallocating their attention towards the positive, rather than the often consistent orientation towards the negative as seen in most patient questionnaires. When we consider what treatments to discuss, we need to know the areas of life from which our patients draw pleasure. The experience of pleasure is what keeps us alive and in pursuit of life. The seeming discomfort and resulting avoidance of medical professionals around the topic of pleasure may be one of the most significant remaining examples of societal stigmas impacting healthcare today. Experience Framework This article is associated with the Policy & Measurement lens of The Beryl Institute Experience Framework (https://theberylinstitute.org/experience-framework/). Access other PXJ articles related to this lens. Access other resources related to this lens.